(NfIZIKA MOLEKUL (B/s - (NlE[E(B, (NaRTURs; (NkR@KOW(B, (Nm(B.(Nw(B.s ((NmOSKWA (B:s (NmIR (B,s, 1987)
(NuKAZ(B. (NHIM(B. (NSOEDINENIJ(B, (NPREDM(B. (NI IMEN(B.: (NS(B. 218-225s
(NsPISOK LIT(B. (NS(B. 216-217s
Artur Losche -
Keywords: (NsWOJSTWA I STRUKTURA MOLEKULQRNYH SISTEMs